Effect of Various Dusts and Humidity on the Performance of Renewable Energy Modules - Anis Ahmad Sher; Naseem Ahmad; Mariyam Sattar; Usman Ghafoor; Umer Hameed Shah (Energies, 2023)
Due to the depletion of fossil fuels, cost-effective and efficient alternate energy resources are a major topic of research nowadays. Solar energy is one of the renewable energy sources which is under research. The main emphasis is on developing new technologies for harnessing the sun’s energy efficiently. Solar photovoltaic (PV) cells are one such technology that works on the principle of the photovoltaic effect, with the electric output generated by it being directly influenced by the amount of light reaching the surface of the cell. Identification of those parameters, which act as an obstacle between light and the solar cell surface and decrease the efficiency of the cell drastically, is necessary. This research study focuses on the environmental parameters (dust and humidity) that directly influence PV cell performance. Here, experiments were conducted by using different types of dusts (sand, soil, ash) of varying quantities and then finding their effect on PV cell output. The results clearly indicate an adverse effect of quantity of dust on performance of the solar PV cell. Moreover, the relative humidity effect on the PV cell performance was also checked, which shows significant change in efficiency for high relative humidity.